Methodological guidelines for the student’s self-study in the course "Information Technology in Economic Activity" - Kovshik, V. I.; Foshchii, P. M. (Національний технічний університет "Харківський політехнічний інститут", 2025)
The methodological guidelines contain questions for independent study by students, assignments and tasks for homework as part of the course “Information Technologies in Economic Activity” in English. Questions for preparation for the final exam and a list of recommended literature and educational resources are also provided.
Keywords: information technology; economic activity; management; hardware; software; internet; spreadsheets; databases; enterprise resource planning systems; cybersecurity; artificial intelligence